2020
DOI: 10.3390/ijms21249603
|View full text |Cite
|
Sign up to set email alerts
|

Cell Sheet Comprised of Mesenchymal Stromal Cells Overexpressing Stem Cell Factor Promotes Epicardium Activation and Heart Function Improvement in a Rat Model of Myocardium Infarction

Abstract: Cell therapy of the post-infarcted myocardium is still far from clinical use. Poor survival of transplanted cells, insufficient regeneration, and replacement of the damaged tissue limit the potential of currently available cell-based techniques. In this study, we generated a multilayered construct from adipose-derived mesenchymal stromal cells (MSCs) modified to secrete stem cell factor, SCF. In a rat model of myocardium infarction, we show that transplantation of SCF producing cell sheet induced activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
(54 reference statements)
0
13
0
1
Order By: Relevance
“…Previously, we examined changes in protein content by mass spectrometry ( Zubkova et al, 2019 ; Dergilev et al, 2020 ) to determine if rAAV infection could induced alteration in MSC EV cargoes and did not find significant differences between EVs from intact or transduced MSC (less than 5% of unique proteins). In the present study, we focused on microRNA content of EVs.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we examined changes in protein content by mass spectrometry ( Zubkova et al, 2019 ; Dergilev et al, 2020 ) to determine if rAAV infection could induced alteration in MSC EV cargoes and did not find significant differences between EVs from intact or transduced MSC (less than 5% of unique proteins). In the present study, we focused on microRNA content of EVs.…”
Section: Resultsmentioning
confidence: 99%
“…Improvement of the methods for the clinical application of MSCs can be associated with the preconditioning of cell cultures in a controlled microenvironment [ 34 , 35 ], the creation of structures (“cell sheets”) of high cell density [ 36 , 37 ], the use of extracellular vesicles of MSCs as a source of trophic factors, cytokines, etc. [ 38 , 39 ], and a number of other approaches.…”
Section: Mesenchymal Stem Cells (Msc)mentioning
confidence: 99%
“…In this regard, the great interest represent studies performed by group of A. Betancourt [ 35 , 36 ]. These authors have shown that MSC preconditioning with proinflammatory factors/cytokines (LPS, TNFalpha, INFgamma) acquire a proinflammatory phenotype, i.e., a capability to express and secrete proinflammatory factors.…”
Section: Immunomodulatory Activity Of Mscmentioning
confidence: 99%
“…Optimization of the recognition of key integrins may be a way for the control of cell retention and differentiation as well as a means of enhancing cell survival in a hypoxic and damaged myocardium and of decreasing secondary migration [34]. Application of stem cells as an epicardial patch after MI may be also a way for controlling cells' microenvironment and preserve their immune functionality after implantation [54,[174][175][176], and thereby possibly a new approach for improving the results of cell therapy after MI.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%